God's relational presence: the cohesive center of biblical theology - Duvall, Jeffrey S. (Baker Academic, a division of Baker Publishing Group, 2019)
The relational presence of God in the Pentateuch -- The relational presence of God in the Historical books, Psalms, and the Wisdom books -- The relational presence of God in the Prophets -- The relational presence of God in Matthew, Mark, and Luke-Acts -- The relational presence of God in Paul's Letters, Hebrews, and the General Letters -- The relational presence of God in John's Gospel, Epistles, and Apocalypse.